Preventing Crypto Scams Through Digital Literacy and Cyber Security - Muhammad Dzaky Maulana; Agus Juhana (International Journal Software Engineering and Computer Science (IJSECS), 2026)
Blockchain-based financial technology has reshaped how digital transactions are conducted, yet its rapid adoption has simultaneously expanded the attack surface for a specific class of cybercrime — cryptocurrency fraud. This study examines how digital literacy education and cybersecurity practices, when applied in combination, can reduce the vulnerability of crypto asset holders to scams. A qualitative approach was adopted through a systematic literature review of prior academic studies alongside an evaluation of fraud cases currently documented in Indonesia. The findings indicate that inadequate digital literacy is the primary driver of user susceptibility to online fraud — users who cannot verify token authenticity, assess transaction risks, or identify phishing attempts are structurally exposed. Applying security measures such as two-factor authentication, data encryption, and strong password management demonstrably reduces that exposure by 50–70%. Coordinating digital literacy education, consumer protection regulation, and cybersecurity awareness is necessary to build a safer and more accountable crypto environment. This study is intended to inform the design of educational programs and national policy on digital asset protection within the broader digital economy